Reaction medium for permeable reactive barrier remediation of groundwater polluted by heavy metals - Li, Hong; Liu, Qingmei (Frontiers in Environmental Science, 2022)
Heavy metal pollution of groundwater has a serious impact on human health, which has become a key issue in the field of water resources and water environment. Permeable reactive barrier (PRB) is an in-situ remediation technology for passive groundwater pollution, with the advantages of economy and efficiency. The reaction material in the PRB wall is the key to the whole system, which can intercept or degrade heavy metals to achieve the removal of pollutants. Among a wide variety of reaction materials, PRB has been successfully used to remove various heavy metal contaminants. In this paper, reaction materials are classified into three broad categories, namely single material, mixed material, and composite material. On this basis, the action mechanism of various materials to remove heavy metal pollutants is analyzed, and the screening method of reaction medium is summarized. Finally, the deficiencies and development directions of PRB reaction medium materials in the removal of heavy metals in groundwater are pointed out, providing reference for the subsequent development and application of PRB reaction medium.